The urban setting thesaurus : a writer's guide to city spaces - Ackerman, Angela, ....-; Puglisi, Becca, ....- ([California] : Writers helping writers, 2016)
Making readers care and feel like they're part of the story should be the number one goal for all writers. Ironically, many storytellers fail to maximize one of fiction's most powerful elements to achieve this: the setting. Not only can the right location become a conduit for emotion, it can also provide conflict, characterize the story's cast, reveal significant backstory, and trigger the reader's own emotional memories through sensory details and deep point of view. Inside The Urban Thesaurus, you'll find: A list of the sights, smells, tastes, textures, and sounds for over 120 urban settings Possible sources of conflict for each location to help you brainstorm ways to naturally complicate matters for your characters Advice on how to make every piece of description count so you can maintain the right pace and keep readers engaged Tips on utilizing the five senses to encourage readers to more fully experience each moment by triggering their own emotional memories Information on how to use the setting to characterize a story's cast through personalization and emotional values while using emotional triggers to steer their decisions A review of specific challenges that arise when writing urban locations, along with common descriptive pitfalls that should be avoided Downloadable tools to help you plan each setting so you can choose the right one for a scene, providing the biggest storytelling punch The Urban Setting Thesaurus helps you tailor each setting to your characters while creating a realistic, textured world readers will long to return to, even after the book closes.
Keywords: English literature